Attitudes Toward Cooperative Strategies: A Cross-Cultural Analysis of Entrepreneurs - Steensma, H Kevin; Marino, Louis; Weaver, K Mark (Journal of International Business Studies, 2000)
Because entrepreneurs mature within a societal context, their attitudes toward cooperation are likely to be influenced by the underlying values of their society. Using a seven-nation sample, we find that entrepreneurs from feminine, collective, and uncertainty-avoiding societies have a greater appreciation for the strategic importance of cooperative strategies than their counterparts. Moreover, entrepreneurs from feminine societies place greater emphasis on partner commonality in terms of objectives and values to ensure cooperative success, whereas those from individualistic societies emphasize contractual safeguards.